Religious Moderation of Nadhlatul Ulama and Muhammadiyah in Combanting Religious Radicalism in Indonesia - Saekul Mujahidin, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Radicalism appears in the form of acts of rejection, resistance, and the desire to change the system or order following the religious doctrines they adhere to. Nahdlatul Ulama (NU) and Muhammadiyah have always voiced the existence of a moderate religion and opposed everything. forms of violence in the name of religion. This study uses a qualitative approach, where all data include; Journals, books, or articles related to this article. The results of the study stated that the notion of radicalism was caused by a narrow interpretation and the incompleteness of the Qur'anic text which then has implications for a wrong understanding of Islamic religious doctrine. Nahdlatul Ulama (NU) and Muhammadiyah strongly oppose the existence of religious radicalism in Indonesia, in overcoming the notion of religious radicalism, NU and Muhammadiyah create cadres in their regions to anticipate the existence of religious radicalism in the general public, the purpose of forming these cadres is to instill Islam. with rules that are appropriate and do not deviate from its teachings, namely Islam Rahmatan Lil Alamin, not only that, NU and Muhammadiyah often voice moderate Islam.